2020
DOI: 10.21203/rs.3.rs-25543/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cardiac rupture complicating acute myocardial infarction: the clinical features from an observational study and animal experiment

Abstract: Background. Cardiac rupture (CR) is a fatal complication of ST-elevation myocardial infarction (STEMI) with its incidence markedly declined in the recent decades. However, clinical features of CR patients now and the effect of reperfusion therapy to CR remain unclear. We investigated the clinical features of CR in STEMI patients and the effect of reperfusion therapy to CR in mice.Methods. Two studies were conducted. In clinical study, data of 1456 STEMI patients admitted to the First Hospital, Xi'an Jiaotong U… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…The early myocardial hemorrhage in CR often leads to a decrease in hemoglobin level (28). In this study, the levels of CK, CK-MB, and NT-proBNP in patients with CR were higher than the control group, which was similar to the results of Lu et al (5), and may be due to the release of more cardiac enzymes, poorer cardiac function, and larger infarct area in patients with CR. Patients in the CR group who underwent emergency PCI had more complex lesions and lower preoperative and postoperative TIMI blood flow grades than the control group, which was similar to the conclusions of Rencuzogullari et al (29).…”
Section: A B Csupporting
confidence: 88%
See 1 more Smart Citation
“…The early myocardial hemorrhage in CR often leads to a decrease in hemoglobin level (28). In this study, the levels of CK, CK-MB, and NT-proBNP in patients with CR were higher than the control group, which was similar to the results of Lu et al (5), and may be due to the release of more cardiac enzymes, poorer cardiac function, and larger infarct area in patients with CR. Patients in the CR group who underwent emergency PCI had more complex lesions and lower preoperative and postoperative TIMI blood flow grades than the control group, which was similar to the conclusions of Rencuzogullari et al (29).…”
Section: A B Csupporting
confidence: 88%
“…Therefore, the early and accurate identification and prevention of possible CR is of great importance. Previous studies found older age, female, lower LVEF, hyperglycemia, and thrombocytopenia were risk factors for CR after AMI (3)(4)(5)(6). These factors were lack of specificity, which often occur in other diseases.…”
Section: Introductionmentioning
confidence: 96%
“…NPAR, composed of neutrophil percentage and albumin, represents two different mechanisms that lead to FWR, and there may be a synergistic effect between them. After the occurrence of AMI, the ischemic myocardial cells are extensively necrotic, which leads to severe inflammatory reaction 19 . Necrotic cardiomyocytes and matrix fragments activate complement amplification cascade reaction and Toll‐IL‐1 receptor pathway, and then nuclear factor (NF)‐κB is activated to induce the secretion of chemokines, cytokines, and adhesion molecules, which leads to neutrophil infiltration 20 .…”
Section: Discussionmentioning
confidence: 99%